Palaeovegetation variation in response to the late Oligocene-early Miocene East Asian summer monsoon in the Ying-Qiong Basin, South China Sea - Ding, Wenjing; Hou, Dujie; Gan, Jun; Wu, Piao; Zhang, Mengting; George, Simon C. (Palaeogeography, palaeoclimatology, palaeoecology, 2021)
Late Oligocene-early Miocene palaeovegetation and palaeoclimate in the Ying-Qiong Basin, South China Sea were comprehensively reconstructed using higher plant-derived biomarkers, palynological records, clay minerals, and kerogen maceral compositions of shales. During the period from about 24.9–18.3 Ma, there are trends of higher relative abundances of plant-derived biomarkers in the younger sediments. Similarly, over this time period there are increasing amounts of tropical/subtropical angiosperms and pteridophytes in the younger sediments, and lesser amounts of temperate Pinus and Alnus species. The bloom of the dominant tropical-subtropical higher plants and the large influx of terrigenous organic matter during this period were likely associated with extra summer monsoonal precipitation under a warming climate. The establishment of the East Asian summer monsoon in the South China Sea is proposed at about 24.9 Ma in the late Oligocene, which is likely to have been caused by uplift of the northern Himalaya-Tibetan Plateau at the same time. •Late Oligocene-early Miocene palaeovegetation variation described in South China Sea.•Higher plant-derived biomarkers, palynological records, clay minerals, macerals used.•Bloom of tropical-subtropical components started from the late Oligocene at ~24.9 Ma.•Establishment of the East Asian summer monsoon proposed at ~24.9 Ma.•Start of E Asian monsoons are close to time of uplift of N Himalaya-Tibetan Plateau.